Phytochemical screening & evaluation of antidiabetic & antihyperlipidemic activity of erythroxylum monogynum in alloxan induced diabetic rats - MEHNOOR FARHEEN; CHAKRAPANI RAMESH (International Journal of Pharma and Bio Sciences, 2017)
The objective of the present study was to evaluate the antidiabetic & antihyperlipidemic activity of Erythroxylum monogynum in alloxan induced diabetic rats. The preliminary phytochemical screening shows the presence of alkaloids, glycosides, carbohydrates, flavonoids, tannins, saponins, sterols & phenols. The antidiabetic & antihyperlipidemic effect of Erythroxylum monogynum was studied in alloxan (150mg/kg b.w., i.p.) induced diabetes in wistar rats for doses 100mg/kg b.w, 200 mg/kg b.w. and 400 mg/kg b.w. (p.o.) daily for 21 days, and the effect was compared with oral dose of 5mg/kg, b.w. glibenclamide. The effect of ethanolic bark extract of Erythroxylum monogynum on blood glucose, serum lipid profile [total cholesterol (TC), triglycerides (TG), high density lipoprotein cholesterol (HDL-C), low density lipoprotein cholesterol (LDL-C), very low density lipoprotein cholesterol (VLDL-C) was measured in the diabetic rats. Diabetes mellitus which was induced by alloxan increase the blood glucose level and other biochemical parameter such as LDLc, VLDLc, TC, total triglycerides and cholesterol ratio and decrese the level of HDLc where as the stem bark ethonolic extract erythroxylum monogynum decreased the level of blood glucose level LDLc, VLDLc, TC, total triglycerides and cholesterol ratio and increased the level of HDLc since HDLc is a good cholesterol indicating erythroxylum monogynum to posses antidiabetic and antihyperlipidimic activity. Ethonolic extract of erythroxylum nonogynum produced it’s effect at all the three doses i.e. 100mg/kg b.w, 200 mg/kg b.w. and 400 mg/kg b.w. (p.o.) daily for 21 days, and the effect was compared with oral dose of 5mg/kg, b.w. glibenclamide, it shown more potent effect at a dose of mg/kg b.w. by reducing blood glucose level by 56%, LDL by 53.82%, VLDL by 37.06%, TC by 31.69%. total triglcerides by 34.85%, cholesterol ratio by 57.81%, when compare to standard drug 58% BGL, LDL by 58.47%, VLDL By 39.64%, TC by 35.34%, TRG by 35.38% and cholesterol ratio by 60.34% respectively.